1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Protein Disulphide Isomerase and Peptides

Abstract: There is growing evidence that protein disulphide isomerase (PDI) has a common chaperone function in the endoplasmic reticulum. To characterise this function, we investigated the interaction of purified PDI with radiolabelled model peptides, somatostatin and mastoparan, by cross-linking. The interaction between the peptides and PDI was specific, for it showed saturation and was abolished by denaturation of PDI. The interaction between a hydrophobic peptide without cysteine residues was much more sensitive to T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
86
2
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 23 publications
13
86
2
3
Order By: Relevance
“…The binding affinity increases with increasing length of the substrate backbone, but for peptides of similar length, those containing Cys residues may bind 4-8-fold more strongly [94,95]. In contrast with earlier data [94], Klappa and co-workers [95] observed that hydrophobic interactions may determine the efficiency of binding.…”
Section: Peptide Bindingcontrasting
confidence: 61%
See 1 more Smart Citation
“…The binding affinity increases with increasing length of the substrate backbone, but for peptides of similar length, those containing Cys residues may bind 4-8-fold more strongly [94,95]. In contrast with earlier data [94], Klappa and co-workers [95] observed that hydrophobic interactions may determine the efficiency of binding.…”
Section: Peptide Bindingcontrasting
confidence: 61%
“…Peptide-binding studies using either somatostatin or a 28-residue peptide from the N-terminus of staphylococcal nuclease indicated that the interaction of peptides with PDI competes with the refolding of reduced, denatured RNase and scrambled RNase, reduces the efficiency of catalysis of insulin reduction, and inhibits the chaperone function of PDI in the refolding of denatured GAPDH [94][95][96]. This indicates not only that both peptide-and polypeptide-binding sites are the same or spatially juxtaposed, but also that they are close enough to the active site to inhibit redox activity when occupied by a polypeptide chain.…”
Section: Peptide Bindingmentioning
confidence: 99%
“…The ER-luminal enzyme and chaperone PDI is the predominant binding partner in the ER lumen for glycosylation acceptor peptides and unglycosylated peptides irrespective of their thiol content (34)(35)(36). PDI is composed of four thioredoxin modules, two enzymatically active ones (a, aЈ) and two inactive ones (b, bЈ) (37).…”
Section: Release From Pdi Is Not Critical For Glycopeptide Export Fromentioning
confidence: 99%
“…Another important group of ER protein-folding enzymes is oxidoreductases that catalyze the formation of disulfide bonds. The best-known member of this group is protein disulfide isomerase (PDI), which recognizes unfolded hydrophobic amino acids on newly synthesized proteins (Freedman et al 2002;Klappa et al 1997). Following the docking with its substrates, PDI is able to oxidize reduced cysteines or isomerize pre-formed disulfide bonds through transient mixed disulfides with its CXXC active sites and substrates (Horibe et al 2004;Walker and Gilbert 1995).…”
Section: Introductionmentioning
confidence: 99%